2011
DOI: 10.1108/03699421111095946
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and performance evaluation of polyurethane/silica hybrid resins

Abstract: Purpose -The aim of this paper is to synthesise polyester/silica hybrid resins and their hybrid polyurethanes via in situ (IS) and blending (BL) methods and to evaluate the effect of preparation method, interaction type and silica content on the physico-chemical and thermal properties of polyurethane/ silica (PU/Silica) hybrid coatings. Design/methodology/approach -Silica particle-containing silica sol was prepared according to Stö ber method using tetraethylorthosilicate as the precursor and then introduced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Athawale and Kulkarni observed that the addition of silica precursors during the polymer synthesis generated stronger polymer‐silica interactions than those obtained when silica was added after the polymer synthesis. These stronger interactions may confer better properties . Similar behavior was reported by Kim et al, who observed an increase in hardness, initial modulus, and strength for tensile and compression loading.…”
Section: Introductionsupporting
confidence: 85%
“…Athawale and Kulkarni observed that the addition of silica precursors during the polymer synthesis generated stronger polymer‐silica interactions than those obtained when silica was added after the polymer synthesis. These stronger interactions may confer better properties . Similar behavior was reported by Kim et al, who observed an increase in hardness, initial modulus, and strength for tensile and compression loading.…”
Section: Introductionsupporting
confidence: 85%
“…The peak placed at 950 cm À1 is related to the stretching vibration of the C-O-C group [31], which is observed in both nafion polymer and composite fiber, confirming silica hybridized with organics. In the case of the composite nanofiber mat, the broad band located at 1080, 790, 480 cm À1 are associated with Si-O-Si stretching vibration of SiO 2 [32]. In order to understand the configuration of composite nanofiber, the flame-treatment was carried out on composite nanofiber mat with directing heating by using the flame of alcohol lamp in air for 30 min and its IR curve is shown in Fig.…”
Section: Ftir Analysismentioning
confidence: 99%
“…Obviously, the decomposition temperature of nafion polymer was dramatically improved due to the hybridization with silica nanofiber. The crucial factor for effecting the nafion decomposition may be related to the structural features of porous nanofiber mats, thermal insulation effect of silica and stronger chemical bonding between silanol group of silica sol and the sulfonic end groups of nafion [32]. The strong chemical bond of nafion/silica interface will contribute to faster energy transformation from polymer surface to silica matrix.…”
Section: Thermal Stability Analysismentioning
confidence: 99%
“…The FTIR transmittance spectra of OWT and PSi are shown in Figure 1 and the assignment of the bands is shown in Table 3 . The characteristic bands almost at 1119, 792, and 466 cm −1 correspond to the stretching, bending and out of plane of Si–O bonds [ 18 , 19 ], respectively, for OWT, and 1088, 795, and 467 cm −1 for PSi. The position and the shape of the main Si–O vibration band at 1119 and 108 cm −1 show a stoichiometric silicon dioxide structure.…”
Section: Resultsmentioning
confidence: 99%
“…This means that OWT is poorly dispersed and interphase adhesion between NR and OWT is weak. Thus, free silica particles with relatively more unreacted hydroxyl groups easily promote aggregation through hydrogen bonding [ 19 ].…”
Section: Resultsmentioning
confidence: 99%